G154(P) Rapid decline of anti-measles antibodies in a cohort of infants from birth to 12 months of age, calls for an urgent change in vaccination strategy in india. (May 2019) - Makam, L; Mathew, J; Ratho, R; Dutta, S; Singh, M; Bharti, B; Suri, V; Massey, D
Abstract : Aim: Since 1985, India has been administering a single dose of measles vaccine to all infants at 9 months of age. This age was chosen to balance the disappearance of maternal (transplacental) antibodies with the increasing risk of developing measles. Measles infection occurs before the age of vaccination in 10%–15% cases, suggesting the absence of immunity well before the age of vaccination. This study was designed to estimate the level of measles specific IgG antibodies in a cohort of term infants followed from birth to 12 months of age; and the pattern of antibody decline in them. Methods: We enrolled a cohort of 168 term infants in a prospective longitudinal study and measured serum IgG anti measles antibody levels (AMAL) at birth, 3 months, 6 months, 9 month (pre-vaccination) and 12 months of age. Maternal serum AMAL was also measured at the time of delivery. Antibody levels>12 U/ml were considered protective. Results: The median (IQR) maternal AMAL at delivery was 66.15 (26.23 to 138.80) and the level in infants at birth was 66.83 (29.04 to 128.79). At birth, 142/168 (84.5%) mothers and 149/168 (88.7%) infants had protective levels. The proportion of protected infants was 25/90 (27.8%) at 3 months, 2/84 (2.38%) at 6 months and 1/34 (2.90%) at 9 months (pre-vaccination). Three months after vaccination, 81.2% infants had protective levels of antibodies whereas 18.8% did not. Conclusion: Measles IgG antibody levels rapidly decline after birth and reach levels far below protective level well before nine months of age. The majority of infants are susceptible as early as 3 months of age, while all are susceptible by 6 months of age. This requires consideration of earlier vaccination to protect these infants, which could have significant public health implications.